(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article provides a methodological analysis of the concepts of "competence", "competence". The competence of the teacher in the formation offunctional literacy of students is analyzed. A functional literate person is the strategic goal of education. Competence of the students in problem solving.